2008
DOI: 10.1111/j.1524-4733.2008.00359.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Atrial Fibrillation on Stroke-Related Inpatient Costs in Sweden: A 3-Year Analysis of Registry Incidence Data from 2001

Abstract: AF-related strokes are associated with higher 3-year inpatient costs than non-AF strokes when controlling for factors such as case fatality rates, other risk factors for stroke, and age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
48
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(52 citation statements)
references
References 14 publications
2
48
1
1
Order By: Relevance
“…12 An analysis from the Swedish Riks-Stroke hospital registry also reported greater acute hospital costs with AF-stroke. 13 Other studies have reported AF-stroke costs as subgroups of cardioembolic stroke or all AF-related costs. 14,15 Although providing valuable information, these studies have excluded patients with stroke and paroxysmal AF, or those with recurrent stroke (which may account for up to one fifth of all AF-stroke), and costs unrelated to acute hospitalization were not described.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…12 An analysis from the Swedish Riks-Stroke hospital registry also reported greater acute hospital costs with AF-stroke. 13 Other studies have reported AF-stroke costs as subgroups of cardioembolic stroke or all AF-related costs. 14,15 Although providing valuable information, these studies have excluded patients with stroke and paroxysmal AF, or those with recurrent stroke (which may account for up to one fifth of all AF-stroke), and costs unrelated to acute hospitalization were not described.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14][15] One study from Germany reported that higher hospital costs were associated with AF-stroke but included only selected hospital-admitted, nonaphasic patients surviving without severe disability at 1 year to provide follow-up interviews. 12 An analysis from the Swedish Riks-Stroke hospital registry also reported greater acute hospital costs with AF-stroke.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations